Characterization of rockfalls from seismic signal: Insights from laboratory experiments. Issue 10 (29th October 2015) - Farin, Maxime; Mangeney, Anne; Toussaint, Renaud; Rosny, Julien de; Shapiro, Nikolai; Dewez, Thomas; Hibert, Clément; Mathon, Christian; Sedan, Olivier; Berger, Frédéric
Abstract: The seismic signals generated by rockfalls can provide information on their dynamics and location. However, the lack of field observations makes it difficult to establish clear relationships between the characteristics of the signal and the source. In this study, scaling laws are derived from analytical impact models to relate the mass and the speed of an individual impactor to the radiated elastic energy and the frequency content of the emitted seismic signal. It appears that the radiated elastic energy and frequencies decrease when the impact is viscoelastic or elastoplastic compared to the case of an elastic impact. The scaling laws are validated with laboratory experiments of impacts of beads and gravels on smooth thin plates and rough thick blocks. Regardless of the involved materials, the masses and speeds of the impactors are retrieved from seismic measurements within a factor of 3. A quantitative energy budget of the impacts is established. On smooth thin plates, the lost energy is either radiated in elastic waves or dissipated in viscoelasticity when the impactor is large or small with respect to the plate thickness, respectively. In contrast, on rough thick blocks, the elastic energy radiation represents less than 5% of the lost energy. Most of the energy is lost in plastic deformation or rotation modes of the bead owing to surface roughness. Finally, we estimate the elastic energy radiated during field scale rockfalls experiments. This energy is shown to be proportional to the boulder mass, in agreement with the theoretical scaling laws. Key Points: Analytical scaling laws relating rockfalls to signal characteristics are derived from impact models The laws are tested for impacts experiments of beads and gravels on various material and geometries An energy budget of the impacts is established among radiated elastic energy and inelastic losses